KOLASE: MENULIS PUISI SECARA ESTAFET DENGAN MENGENALKAN KEBUDAYAAN “MENGGELEK TOBU” DARI KUOK DI KELAS - Juliana Juliana; Hasnah Faizah; Elmustian Rahman; Syafrial Syafrial (KOLASE, 2022)
This research discusses writing poetry in relay using the "gelek tobu" culture of the quok in class, with the aim of this research being to be able to write down or express thoughts and feelings through beautiful dictions. So that what is felt, reaches the reader. Research using qualitative research methods is divided into two scopes, namely library research and field research. Library research relies almost entirely on data from libraries, so this research is more popularly known as qualitative descriptive literature research or bibliographical research. In addition, library research is often termed non-reactive research, because it only relies on theoretical data and documentation in the library. The results of research conducted One of the innovative learning models is the process approach combined with active, innovative, creative, effective, and fun learning as described above. However, these are not the only models that are the best and most suitable. There are still many other learning models whose presence is also very much needed to support the success of learning, especially in learning Indonesian at school. The use of innovative techniques and methods in learning Indonesian can certainly create a conducive learning situation. Students in this regard are directly involved in absorbing information. Through a dynamic Indonesian learning process, it is hoped that a form of oral communication will be created between students and other students who are patterned through listening, speaking, reading, and writing skills so that the learning atmosphere is avoided from saturation.